Cocrystal formation by anti-solvent slurry - Li, Yi; Li, Shun-Yu; Dai, Xia-Lin; Lu, Tong-Bu; Chen, Jia-Mei (CrystEngComm, 2023)
An anti-solvent slurry method for cocrystal formation is developed and tested in 25 carbamazepine cocrystal systems. With a low solvent/anti-solvent volume ratio, it reduces solubility of reactants and products, and levels out solubility difference of reactants, and consequently generates cocrystals with a higher success rate, higher purity and higher yield than commonly used slurry methods. An anti-solvent slurry method for cocrystal formation is developed and tested in 25 carbamazepine cocrystal systems, which reveals that it is a facile, efficient and reliable method for cocrystal discovery and synthesis.